The impact of insurance on the economic development: Case study in Armenia - Voskanyan, Gohar; Manucharyan, Meri; Khachatryan, Liana; Kocharyan, Tsovinar; Matinyan, Alvard (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the article is to reveal the connection between the country’s economic development and the insurance system and to present clear recommendations for the development of the insurance system. To achieve the set goal, the task was set to study the approaches of various authors on the topic, present the main indicators characterizing the Armenian insurance market, the problems existing in the sector, and propose options for their solution. Deductive, historical, comparative, statistical, mathematical, and forecasting methods were used for research and analysis. As a result of the studies conducted, it has become clear that there is a positive relationship between the economic development of the country and the insurance system. As a result of the studies, it became clear that the Armenian insurance market has development trends. However, when we compare the main indicators characterizing the insurance sector with those of developed countries and neighboring countries, it is noticeable that Armenia lags behind the mentioned countries. The article highlights the obstacles that hinder the development of the insurance system. The practical application of the recommendations presented in the article by the relevant competent authorities will contribute to the development of the insurance system, which in turn will contribute to the economic development of the country.